High-conductivity thermosetting resin-based composite material and preparation method thereof

By introducing a variety of conductive fillers and reinforcement materials into the thermosetting resin-based composite materials, a multi-layer conductive network and three-dimensional network structure is solved, and the problem of existing materials being difficult to meet high conductivity and other comprehensive performances at the same time is realized, and a high-performance conductive composite material is achieved.

CN119823530AActive Publication Date: 2025-04-15GONGSHENG (TIANJIN) NEW MATERIAL TECH PARTNERSHIP (LLP)

Patent Information

Application Number
CN202510033314.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Existing conductive composite materials are difficult to meet the requirements of high conductivity and other comprehensive performance at the same time, especially in the fields of electronic devices packaging and electromagnetic shielding.

Method used

By introducing a variety of conductive fillers and reinforcement materials into thermosetting resin-based composite materials, including conductive carbon nanotubes, nanosilver particles, conductive polymer microspheres, graphene nanosheets, aluminum borate whiskers and barium titanate nanoparticles, a multi-layer conductive network and three-dimensional network structure are formed to optimize the overall performance of the material.

Benefits of technology

It achieves high conductivity, good mechanical properties, heat resistance and dielectric properties, making the materials suitable for electronic packaging, sensors, electromagnetic shielding and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823530A_ABST
    Figure CN119823530A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, in particular to a high-conductivity thermosetting resin-based composite material and a preparation method thereof.The high-conductivity thermosetting resin-based composite material is prepared from, by weight, 50-80 parts of epoxy resin, 10-30 parts of conductive carbon nanotubes, 20-40 parts of nano-silver particles, 10-20 parts of functionalized polyurethane prepolymer, 5-15 parts of polyamine curing agent and 2-8 parts of organosilane coupling agent. 5-15 parts of graphene nanosheets, 5-15 parts of aluminum borate whiskers and 5-15 parts of barium titanate nanoparticles; 2-10 parts of conductive polymer microspheres; 1 to 5 parts of nano zinc oxide; wherein the conductive polymer microsphere comprises a core formed by polyaniline or polypyrrole, and a polyurethane polymer or a polyacrylate polymer wrapping the outer layer of the core; the surface of the core is modified by adopting nano silver particles and gamma-aminopropyltriethoxysilane; the conductive polymer microspheres are used for providing a long-range conductive path, the nano-silver particles are used for providing short-range conductive connection, and the conductive polymer microspheres and the nano-silver particles form a multi-layer conductive network.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, specifically to a highly conductive thermosetting resin-based composite material and its preparation method. Background Technology

[0002] As electronic devices evolve towards miniaturization, integration, and high performance, higher demands are being placed on packaging materials. While traditional metal materials possess excellent conductivity, they are heavy, complex to process, and susceptible to environmental influences. Therefore, developing lightweight, high-performance conductive composite materials has become a research hotspot. Conductive composite materials can achieve high conductivity by introducing conductive fillers, such as carbon nanotubes and silver particles, into a polymer matrix. However, a single conductive filler often struggles to simultaneously meet the requirements of high conductivity and other comprehensive performance characteristics; therefore, the synergistic effect of multiple fillers is needed to optimize the overall performance of the composite material. Summary of the Invention

[0003] To address the shortcomings of existing technologies, this invention provides a highly conductive thermosetting resin-based composite material and its preparation method. This composite material possesses excellent electrical conductivity, mechanical properties, heat resistance, and dielectric properties, making it suitable for applications such as electronic packaging, sensors, and electromagnetic shielding.

[0004] According to a first aspect of the present invention, a highly conductive thermosetting resin-based composite material is provided, the composite material comprising, by weight, the following components:

[0005] 50-80 parts epoxy resin,

[0006] 10-30 parts of conductive carbon nanotubes

[0007] 20-40 parts of nano silver particles,

[0008] 10-20 parts of functionalized polyurethane prepolymer,

[0009] 5-15 parts of polyamine curing agent

[0010] 2-8 parts of organosilane coupling agent

[0011] 5-15 parts of graphene nanosheets

[0012] 5-15 parts of aluminum borate whiskers,

[0013] 5-15 parts of barium titanate nanoparticles;

[0014] 2-10 parts of conductive polymer microspheres;

[0015] Nano zinc oxide: 1-5 parts;

[0016] The conductive polymer microspheres include a core made of polyaniline or polypyrrole, and a polyurethane polymer or polyacrylate polymer wrapped around the core.

[0017] The core surface is modified with silver nanoparticles and γ-aminopropyltriethoxysilane;

[0018] The conductive polymer microspheres provide long-range conductive paths, while the silver nanoparticles provide short-range conductive connections. The conductive polymer microspheres and the silver nanoparticles form a multi-layered conductive network.

[0019] According to embodiments of the present invention, the conductive polymer microspheres not only possess excellent electrical conductivity but also exhibit a unique synergistic effect in thermosetting resin-based composite materials. A core composed of polyaniline or polypyrrole has conductive properties, while polyurethane polymers or polyacrylate polymers enhance the dispersibility and compatibility of the microspheres in epoxy resin. Nanoparticles of silver are introduced onto the surface of the conductive polymer microspheres, forming a core-shell-satellite structure. These nanoparticles not only further enhance electrical conductivity but also improve the interfacial contact between the microspheres and other conductive fillers (such as carbon nanotubes and graphene nanosheets).

[0020] The core conductive polymer provides a long-range conductive path, while the surface nano-silver particles provide short-range conductive connections. Together, they form a multi-layered conductive network, which significantly improves the overall conductivity of the composite material. The functional polymer shell and surface functionalization treatment enhance the dispersibility and compatibility of the conductive polymer microspheres in the epoxy resin, reduce the aggregation of microspheres, and ensure a uniform conductive distribution.

[0021] There is a synergistic effect between conductive polymer microspheres and other conductive fillers such as carbon nanotubes and graphene nanosheets. The microspheres can fill the gaps between these fillers, forming a more continuous and stable conductive network, thereby improving the conductivity and mechanical strength of the composite material. In addition to conductivity, conductive polymer microspheres can also endow the composite material with additional functions, such as antistatic properties and electromagnetic shielding properties, broadening the application fields of the material.

[0022] According to an embodiment of the present invention, the epoxy resin is a bisphenol A type epoxy resin and / or a bisphenol F type epoxy resin.

[0023] According to an embodiment of the present invention, the conductive carbon nanotubes are surface treated to introduce carboxyl and hydroxyl groups on the surface of the carbon nanotubes, thereby improving dispersibility and conductivity. The surface modifier is selected from one or more combinations of aminosilanes, epoxysilanes, and carboxylsilanes.

[0024] According to embodiments of the present invention, oxygen-containing functional groups such as carboxyl groups (-COOH) and hydroxyl groups (-OH) are introduced onto the surface of carbon nanotubes through chemical oxidation. These functional groups can enhance the compatibility between CNTs and the resin matrix and reduce the aggregation of CNTs.

[0025] According to an embodiment of the present invention, the functionalized polyurethane prepolymer contains active groups that can react with epoxy resin;

[0026] The functionalized polyurethane prepolymer contains terminal hydroxyl or amine groups, which can undergo crosslinking reactions with epoxy resin.

[0027] The active groups in the functionalized polyurethane prepolymer undergo a cross-linking reaction with the epoxy resin, forming a stable three-dimensional network structure, which further improves the mechanical properties of the composite material.

[0028] According to an embodiment of the present invention, the polyamine curing agent has at least three amine reaction sites, enabling rapid curing at lower temperatures.

[0029] According to an embodiment of the present invention, the polyamine curing agent is selected from one or more combinations of diethylenetriamine, triethylenetetraamine, and tetraethylenepentamine.

[0030] According to an embodiment of the present invention, the organosilane coupling agent is used to improve the interfacial compatibility between the conductive filler and the resin matrix.

[0031] According to embodiments of the present invention, the organosilane coupling agent is selected from one or more combinations of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane.

[0032] According to embodiments of the present invention, graphene nanosheets, as auxiliary conductive fillers, work together with conductive carbon nanotubes and silver nanoparticles to further enhance the conductivity of the composite material.

[0033] According to embodiments of the present invention, aluminum borate whiskers are used as a reinforcing material, which can significantly improve the mechanical strength and heat resistance of the composite material.

[0034] According to embodiments of the present invention, barium titanate nanoparticles not only provide additional conductive paths but also enhance the dielectric properties of the material. Furthermore, they work synergistically with aluminum borate whiskers to further improve the overall performance of the composite material.

[0035] According to an embodiment of the present invention, the composite material can be cured between room temperature and 100°C, and the cured composite material has good mechanical properties, electrical conductivity, and a volume resistivity of less than 1×10⁻⁶. -4 It exhibits excellent heat resistance, impact resistance and dielectric properties, with a strength of Ω·cm.

[0036] According to an embodiment of the present invention, the graphene nanosheets have a thickness of 0.3-10 nanometers and a diameter of 1-10 micrometers.

[0037] Multiple conductive pathways: Conductive carbon nanotubes, silver nanoparticles, and graphene nanosheets form multiple conductive pathways, which improves the conductivity of the composite material.

[0038] Interface effect: Organosilane coupling agents improve the interfacial compatibility between conductive fillers and resin matrix, reduce interfacial defects, and improve conductivity.

[0039] According to an embodiment of the present invention, the aluminum borate whiskers have a length of 10-100 micrometers and a diameter of 0.1-1 micrometers.

[0040] According to an embodiment of the present invention, the barium titanate nanoparticles have a particle size of 50-500 nanometers.

[0041] Aluminum borate whiskers and barium titanate nanoparticles, used as reinforcing materials, significantly improve the mechanical strength and toughness of the composite material. Both exhibit good thermal stability, allowing the composite material to maintain good mechanical properties at high temperatures. Barium titanate nanoparticles possess a high dielectric constant, significantly enhancing the dielectric properties of the composite material.

[0042] According to a second aspect of the present invention, a method for preparing a highly conductive thermosetting resin-based composite material is provided, comprising the following steps:

[0043] Preparation of conductive polymer microspheres;

[0044] Epoxy resin, conductive carbon nanotubes, silver nanoparticles, functionalized polyurethane prepolymer, organosilane coupling agent, graphene nanosheets, aluminum borate whiskers, the conductive polymer microspheres, zinc oxide nanoparticles, and barium titanate nanoparticles are mixed evenly to obtain a premix.

[0045] Add a polyamine curing agent to the premix and continue stirring until homogeneous to obtain a composite material slurry;

[0046] The composite material slurry is poured into a mold and cured at a temperature between room temperature and 100°C to obtain the highly conductive thermosetting resin-based composite material.

[0047] According to embodiments of the present invention, a method for preparing a highly conductive thermosetting resin-based composite material is provided, specifically including the following steps: adding epoxy resin, conductive carbon nanotubes, silver nanoparticles, functionalized polyurethane prepolymer, organosilane coupling agent, graphene nanosheets, aluminum borate whiskers, and barium titanate nanoparticles into a high-speed shear mill or a planetary mixer.

[0048] At room temperature, turn on a high-speed shear mixer or planetary mixer and mix at a speed of 3000-5000 rpm for 10-60 minutes until all components are evenly dispersed to obtain a premix.

[0049] Slowly add the polyamine curing agent to the premixed material. Continue stirring in a high-speed shear mixer or planetary mixer at a speed of 3000-5000 rpm for 5-15 minutes to ensure uniform distribution of the curing agent and obtain the composite material slurry.

[0050] Pour the composite slurry into a pre-prepared mold. Place the mold in a temperature-controlled oven and cure at a temperature between room temperature and 100°C. Cure at room temperature for 2-4 hours, then raise the temperature to 60°C and continue curing for another 2-4 hours. Alternatively, cure directly at 60-100°C for 2-4 hours. After curing, remove the composite material from the mold and allow it to cool naturally.

[0051] According to embodiments of the present invention, necessary post-processing, such as grinding and cutting, can also be performed on the cured composite material to meet specific application requirements.

[0052] The above detailed preparation method can yield thermosetting resin-based composite materials with high electrical conductivity, good mechanical properties, heat resistance, and dielectric properties. This method ensures the uniformity and consistency of the composite material by precisely controlling the proportions of each component and the mixing process, thereby improving the performance of the final product.

[0053] According to an embodiment of the present invention, the mixing process is carried out in a high-speed shear machine or a planetary mixer, and the mixing time is 10-60 minutes.

[0054] According to an embodiment of the present invention, the preparation of conductive polymer microspheres includes:

[0055] Preparation core:

[0056] A aniline or pyrrole, along with ammonium persulfate, is dissolved in deionized water at a molar ratio of 1:1 to form a homogeneous aniline monomer solution, a pyrrole monomer solution, and an ammonium persulfate aqueous solution.

[0057] A certain amount of sodium dodecylbenzenesulfonate is added to the aniline monomer solution or pyrrole monomer solution as a stabilizer to prevent particle aggregation during polymerization.

[0058] A aniline monomer solution or pyrrole monomer solution and ammonium persulfate aqueous solution are mixed in an ice bath and stirred continuously at 0-5°C for 24 hours to obtain the core.

[0059] Surface modification of the core:

[0060] A certain amount of silver nitrate is dissolved in deionized water to form a silver ion solution;

[0061] Prepare a reducing agent solution, disperse the core in a silver ion solution, and sonicate to ensure uniform dispersion;

[0062] Slowly add the reducing agent solution while stirring to reduce silver ions to nano-silver particles on the core surface;

[0063] After the reaction is complete, the modified core is collected by centrifugation and repeatedly washed with deionized water to remove unreacted silver salts and reducing agents; finally, the core is dried in a vacuum drying oven for later use.

[0064] Surface grafting is performed on the core:

[0065] An appropriate amount of γ-aminopropyltriethoxysilane was dissolved in anhydrous ethanol to form a modified solution;

[0066] The modified core was dispersed in a modified solution and ultrasonically treated to ensure uniform dispersion.

[0067] Allow the mixture to stand at room temperature for a period of time (e.g., 12 hours) to allow the silane coupling agent to undergo a chemical grafting reaction with the core surface.

[0068] After the reaction was completed, the functionalized microsphere cores were collected by centrifugation and repeatedly washed with anhydrous ethanol to remove unreacted silane coupling agent.

[0069] Finally, the microsphere cores were dried in a vacuum drying oven for later use, resulting in the modified cores.

[0070] Core Encapsulation:

[0071] Polyurethane prepolymer or polyacrylate prepolymer is dissolved in tetrahydrofuran to form a prepolymer solution.

[0072] Add an appropriate amount of crosslinking agent as needed to promote subsequent crosslinking reactions;

[0073] The functionalized core is dispersed in a prepolymer solution and ultrasonically treated to ensure uniform dispersion.

[0074] Allow the prepolymer to stand at room temperature for a period of time (e.g., 6 hours) to allow it to undergo a cross-linking reaction on the core surface, forming a polymer shell.

[0075] After the reaction was completed, the coated conductive polymer microspheres were collected by centrifugation and repeatedly washed with tetrahydrofuran to remove unreacted prepolymer and crosslinking agent.

[0076] The conductive polymer microspheres were obtained by drying.

[0077] According to an embodiment of the present invention, the reducing agent solution is either sodium citrate or sodium borohydride.

[0078] The detailed preparation method described above successfully produces conductive polymer microspheres with innovative characteristics. These microspheres not only possess excellent electrical conductivity but also exhibit unique synergistic effects in thermosetting resin-based composite materials, significantly enhancing the overall performance of the materials. This method is suitable for large-scale industrial production and has broad application prospects and market potential.

[0079] The highly conductive thermosetting resin-based composite material provided by this invention achieves high conductivity, good mechanical properties, heat resistance, and dielectric properties by introducing various conductive fillers and reinforcing materials. In particular, the synergistic effect of introducing barium titanate nanoparticles, conductive polymer microspheres, and aluminum borate whiskers further enhances the overall performance of the composite material, enabling it to exhibit excellent characteristics in multiple aspects. Furthermore, the preparation method of this invention is simple, easy to industrialize, and has high practical value. Attached Figure Description

[0080] Figure 1 This is a flowchart illustrating the preparation process of the highly conductive thermosetting resin-based composite material according to an embodiment of the present invention. Detailed Implementation

[0081] This application provides embodiments of highly conductive thermosetting resin-based composite materials and their preparation methods. Detailed Implementation

[0083] The premix was prepared using the following method:

[0084] The raw materials are added to a high-speed shear mill and mixed at a speed of 4000 rpm for 30 minutes until all components are evenly dispersed to obtain a premix.

[0085] During the mixing process, conductive carbon nanotubes and silver nanoparticles tend to agglomerate. High-speed shearing can effectively break up these agglomerates, ensuring their uniform dispersion within the resin matrix. Furthermore, the addition of organosilane coupling agents helps improve the interfacial compatibility between the conductive filler and the resin matrix, thereby enhancing the mechanical properties of the composite material.

[0086] Add curing agent:

[0087] Triethylenetetramine was slowly added to the premixed material.

[0088] Continue stirring in the high-speed shear machine at a speed of 4000 rpm for 10 minutes to ensure uniform distribution of the curing agent and obtain the composite material slurry.

[0089] Triethylenetetramine is a highly efficient curing agent that can rapidly cure epoxy resins at lower temperatures, thereby shortening curing time and improving production efficiency.

[0090] Pouring and curing:

[0091] The composite slurry is poured into a pre-prepared mold.

[0092] Place the mold in a constant temperature chamber and cure it at 60°C for 3 hours.

[0093] After curing, the composite material is removed from the mold and allowed to cool naturally.

[0094] During the curing process, the active groups in the functionalized polyurethane prepolymer undergo a cross-linking reaction with the epoxy resin to form a three-dimensional network structure, thereby improving the toughness of the composite material. Simultaneously, the addition of barium titanate nanoparticles and aluminum borate whiskers not only provides additional conductive pathways but also enhances the dielectric and mechanical properties of the material.

[0095] Post-processing:

[0096] After curing, the composite material undergoes necessary post-processing, such as grinding and cutting, to meet specific application requirements.

[0097] The preparation of conductive polymer microspheres includes:

[0098] Preparation core:

[0099] Aniline or pyrrole and ammonium persulfate are dissolved in deionized water at a molar ratio of 1:1 to form a homogeneous aniline monomer solution or pyrrole monomer solution and ammonium persulfate aqueous solution.

[0100] A certain amount of sodium dodecylbenzenesulfonate is added to the aniline monomer solution or pyrrole monomer solution as a stabilizer to prevent particle aggregation during polymerization.

[0101] A aniline monomer solution or pyrrole monomer solution and ammonium persulfate aqueous solution are mixed in an ice bath and stirred continuously at 0-5°C for about 24 hours to obtain the core.

[0102] Surface modification of the core:

[0103] A certain amount of silver nitrate is dissolved in deionized water to form a silver ion solution; an appropriate amount of reducing agent (such as sodium citrate or sodium borohydride) solution is prepared, and the pre-prepared core is dispersed in the silver ion solution and ultrasonically treated to ensure uniform dispersion.

[0104] Slowly add the reducing agent solution while stirring to reduce silver ions to nano-silver particles on the core surface;

[0105] After the reaction is complete, the modified cores are collected by centrifugation and repeatedly washed with deionized water to remove unreacted silver salts and reducing agents; finally, the cores are dried in a vacuum drying oven for later use.

[0106] Surface grafting is performed on the core:

[0107] An appropriate amount of γ-aminopropyltriethoxysilane was dissolved in anhydrous ethanol to form a modified solution;

[0108] The modified core was dispersed in the modified solution and ultrasonically treated to ensure uniform dispersion.

[0109] Allow the silane coupling agent to stand at room temperature for a period of time (e.g., 12 hours) to undergo a chemical grafting reaction with the core surface.

[0110] After the reaction was completed, the functionalized cores were collected by centrifugation and washed repeatedly with anhydrous ethanol to remove unreacted silane coupling agent.

[0111] Finally, the core was dried in a vacuum drying oven for later use, resulting in the modified core.

[0112] Core Encapsulation:

[0113] Polyurethane prepolymer or polyacrylate prepolymer is dissolved in tetrahydrofuran to form a prepolymer solution.

[0114] Add an appropriate amount of crosslinking agent as needed to promote subsequent crosslinking reactions;

[0115] The core is dispersed in the prepolymer solution and ultrasonically treated to ensure uniform dispersion.

[0116] Allow the prepolymer to stand at room temperature for a period of time (e.g., 6 hours) to allow it to undergo a cross-linking reaction on the surface of the microspheres, forming a polymer shell.

[0117] After the reaction was completed, the coated conductive polymer microspheres were collected by centrifugation and repeatedly washed with tetrahydrofuran to remove unreacted prepolymer and crosslinking agent.

[0118] Finally, the microspheres were dried in a vacuum drying oven for later use, resulting in the conductive polymer microspheres.

[0119] Example 1

[0120] Epoxy resin: 60 parts of bisphenol A

[0121] Conductive carbon nanotubes (surface treated): 20 parts

[0122] Nano silver particles: 30 parts

[0123] Functionalized polyurethane prepolymer: 15 parts

[0124] Triethylenetetramine curing agent: 10 parts

[0125] γ-aminopropyltriethoxysilane coupling agent: 5 parts

[0126] Graphene nanosheets: 10 parts

[0127] Aluminum borate whiskers: 10 parts

[0128] Barium titanate nanoparticles: 10 parts

[0129] Conductive polymer microspheres: 5 parts

[0130] Nano zinc oxide: 3 parts

[0131] Example 2

[0132] Epoxy resin: 70 parts of bisphenol F type

[0133] Conductive carbon nanotubes (surface treated): 25 parts

[0134] Nano silver particles: 35 parts

[0135] Functionalized polyurethane prepolymer: 18 parts

[0136] Diethylenetriamine curing agent: 12 parts

[0137] γ-glycidyl oxypropyltrimethoxysilane coupling agent: 6 parts; graphene nanosheets: 12 parts

[0138] Aluminum borate whiskers: 12 parts

[0139] Barium titanate nanoparticles: 12 parts

[0140] Conductive polymer microspheres: 8 parts

[0141] Nano zinc oxide: 4 parts

[0142] Example 3

[0143] Epoxy resin: 55 parts of bisphenol A

[0144] Conductive carbon nanotubes (surface treated): 25 parts

[0145] Nano silver particles: 35 parts

[0146] Functionalized polyurethane prepolymer: 20 parts

[0147] Triethylenetetramine curing agent: 12 parts

[0148] γ-aminopropyltriethoxysilane coupling agent: 6 parts

[0149] Graphene nanosheets: 12 parts

[0150] Aluminum borate whiskers: 10 parts

[0151] Barium titanate nanoparticles: 10 parts

[0152] Conductive polymer microspheres: 10 parts

[0153] Nano zinc oxide: 5 parts

[0154] Example 4

[0155] Epoxy resin: 75 parts of bisphenol F type

[0156] Conductive carbon nanotubes (surface treated): 20 parts

[0157] Nano silver particles: 30 parts

[0158] Functionalized polyurethane prepolymer: 15 parts

[0159] Tetraethylenepentamine curing agent: 10 parts

[0160] γ-Methacryloxypropyltrimethoxysilane coupling agent: 5 parts; Graphene nanosheets: 10 parts

[0161] Aluminum borate whiskers: 15 parts

[0162] Barium titanate nanoparticles: 15 parts

[0163] Conductive polymer microspheres: 2 parts

[0164] Nano zinc oxide: 1 part

[0165] Comparative Example

[0166] Comparative Example 1 (without conductive polymer microspheres)

[0167] Epoxy resin: 60 parts of bisphenol A

[0168] Conductive carbon nanotubes (surface treated): 20 parts

[0169] Nano silver particles: 30 parts

[0170] Functionalized polyurethane prepolymer: 15 parts

[0171] Triethylenetetramine curing agent: 10 parts

[0172] γ-aminopropyltriethoxysilane coupling agent: 5 parts

[0173] Graphene nanosheets: 10 parts

[0174] Aluminum borate whiskers: 10 parts

[0175] Barium titanate nanoparticles: 10 parts

[0176] Nano zinc oxide: 3 parts

[0177] Comparative Example 2 (without nano zinc oxide)

[0178] Epoxy resin: 70 parts of bisphenol F type

[0179] Conductive carbon nanotubes (surface treated): 25 parts

[0180] Nano silver particles: 35 parts

[0181] Functionalized polyurethane prepolymer: 18 parts

[0182] Diethylenetriamine curing agent: 12 parts

[0183] γ-glycidyl oxypropyltrimethoxysilane coupling agent: 6 parts

[0184] Graphene nanosheets: 12 parts

[0185] Aluminum borate whiskers: 12 parts

[0186] Barium titanate nanoparticles: 12 parts

[0187] Conductive polymer microspheres: 8 parts

[0188] Comparative Example 3 (without conductive polymer microspheres and nano zinc oxide)

[0189] Epoxy resin: 55 parts of bisphenol A

[0190] Conductive carbon nanotubes (surface treated): 25 parts

[0191] Nano silver particles: 35 parts

[0192] Functionalized polyurethane prepolymer: 20 parts

[0193] Triethylenetetramine curing agent: 12 parts

[0194] γ-aminopropyltriethoxysilane coupling agent: 6 parts

[0195] Graphene nanosheets: 12 parts

[0196] Aluminum borate whiskers: 10 parts

[0197] Barium titanate nanoparticles: 10 parts

[0198] Performance testing

[0199] Conductivity test: The volume resistivity of the composite material was determined using the four-probe method.

[0200] Mechanical property testing: Tensile strength test shall be conducted in accordance with GB / T 1447-2005 standard.

[0201] Heat resistance test: The glass transition temperature (Tg) of the composite material was determined using differential scanning calorimetry (DSC).

[0202] Dielectric property testing: The dielectric constant and dielectric loss of the composite material were determined using a dielectric spectrometer, and the results are shown in Table 1.

[0203] Table 1. Performance test results of Examples 1-4 and Comparative Examples 1-3

[0204]

[0205]

[0206] Data Analysis and Conclusions

[0207] The table above provides a clear comparison of the curing conditions and corresponding performance test results for the four embodiments. A detailed analysis follows:

[0208] Electrical conductivity:

[0209] The volume resistivity of Examples 1 to 4 is 8.5 × 10⁻⁶. -5 Ω·cm, 7.2×10 -5 Ω·cm, 7.0×10 -5 Ω·cm and 7.5×10 -5 The Ω·cm indicates that all formulations have good electrical conductivity.

[0210] Example 3 exhibits the lowest volume resistivity, indicating that it has the best conductivity; while Comparative Examples 1 and 3 have higher volume resistivity, indicating that the addition of conductive polymer microspheres and nano zinc oxide significantly improves conductivity.

[0211] Mechanical properties:

[0212] The tensile strengths of Examples 1 to 4 were 75 MPa, 80 MPa, 82 MPa and 85 MPa, respectively, indicating that Example 4 had the highest mechanical strength.

[0213] The low tensile strength of Comparative Examples 1 and 3 indicates that the addition of conductive polymer microspheres and nano zinc oxide helps to improve the toughness of the material.

[0214] Heat resistance:

[0215] The glass transition temperatures (Tg) of Examples 1 to 4 were 120°C, 125°C, 122°C and 130°C, respectively, indicating that Example 4 had the best stability at high temperatures.

[0216] The lower Tg values ​​of Comparative Examples 1 and 3 indicate that the addition of conductive polymer microspheres and nano zinc oxide helps to improve the heat resistance of the materials.

[0217] Dielectric properties:

[0218] The dielectric constants of Examples 1 to 4 are 15.2, 16.5, 15.8 and 17.0, respectively, and the dielectric losses are 0.02, 0.018, 0.019 and 0.017, respectively.

[0219] Example 4 exhibits the highest dielectric constant and the lowest dielectric loss, indicating that it has the best dielectric performance. In contrast, Comparative Examples 1 and 3 have poor dielectric performance, suggesting that the addition of conductive polymer microspheres and nano zinc oxide helps to improve dielectric performance.

[0220] in conclusion

[0221] Through systematic design and experimental verification, a variety of highly conductive thermosetting resin-based composite materials have been successfully developed. These materials not only possess excellent electrical conductivity but also good mechanical properties, heat resistance, and dielectric properties, making them suitable for electronic packaging, sensors, electromagnetic shielding, and other fields. Experimental data show that different formulations have a significant impact on the performance of the composite materials, with Example 4 exhibiting the best performance across multiple performance indicators and demonstrating the broadest application prospects. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

[0222] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A highly conductive thermosetting resin-based composite material, characterized in that: The composite material comprises the following components by weight: Epoxy resin 50-80 parts, 10-30 parts of conductive carbon nanotubes, 20-40 parts of nano silver particles, 10-20 parts of functionalized polyurethane prepolymer, 5-15 parts of polyamine curing agent, 2-8 parts of organic silane coupling agent, 5-15 parts of graphene nanosheets, Aluminum borate whiskers 5-15 parts, 5-15 parts of barium titanate nanoparticles; 2-10 parts of conductive polymer microspheres; Nano zinc oxide: 1-5 parts; Wherein, the conductive polymer microspheres include a core composed of polyaniline or polypyrrole, and a polyurethane polymer or polyacrylate polymer wrapped in the outer layer of the core; The core surface is modified with nano silver particles and γ-aminopropyltriethoxysilane; The conductive polymer microspheres are used to provide long-range conductive paths, the nano-silver particles are used to provide short-range conductive connections, and the conductive polymer microspheres and the nano-silver particles form a multi-level conductive network.

2. A highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The conductive carbon nanotubes are surface-modified to introduce carboxyl groups and hydroxyl groups on the surfaces of the carbon nanotubes, and the surface modifier is selected from one or more combinations of aminosilane, epoxysilane, and carboxylsilane.

3. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The functionalized polyurethane prepolymer contains terminal hydroxyl groups or amine groups and can undergo cross-linking reaction with epoxy resin.

4. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The polyamine curing agent is selected from one or more combinations of diethylenetriamine, triethylenetetramine and tetraethylenepentamine.

5. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The organic silane coupling agent is selected from one or more combinations of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; The epoxy resin is bisphenol A epoxy resin and / or bisphenol F epoxy resin.

6. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The graphene nanosheet has a thickness of 0.3-10 nanometers and a sheet diameter of 1-10 micrometers.

7. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The aluminum borate whisker has a length of 10-100 microns and a diameter of 0.1-1 microns.

8. The highly conductive thermosetting resin-based composite material according to claim 1, characterized in that: The particle size of the barium titanate nanoparticles is 50-500 nanometers.

9. A method for preparing a highly conductive thermosetting resin-based composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of conductive polymer microspheres; Evenly mixing epoxy resin, conductive carbon nanotubes, nanosilver particles, functionalized polyurethane prepolymer, organic silane coupling agent, graphene nanosheets, aluminum borate whiskers, the conductive polymer microspheres, nano zinc oxide and barium titanate nanoparticles to obtain a premix; Adding a polyamine curing agent to the premix, and continuing to stir evenly to obtain a composite material slurry; The composite material slurry is poured into a mold and cured at a temperature between room temperature and 100° C. to obtain the highly conductive thermosetting resin-based composite material.

10. The preparation method according to claim 9, characterized in that: The preparation of conductive polymer microspheres comprises: Preparation of the core: Dissolving aniline or pyrrole and ammonium persulfate in deionized water at a molar ratio of 1:1 to form a uniform aniline monomer solution or pyrrole monomer solution and an ammonium persulfate aqueous solution; Adding a certain amount of sodium dodecylbenzene sulfonate as a stabilizer to the aniline monomer solution or the pyrrole monomer solution to prevent agglomeration of particles during the polymerization process; Mixing the aniline monomer solution or the pyrrole monomer solution and the ammonium persulfate aqueous solution under ice bath conditions, and continuously stirring the mixture at a temperature between 0 and 5° C. for 24 hours to obtain the core; The core is surface modified: A certain amount of silver nitrate is dissolved in deionized water to form a silver ion solution; preparing a reducing agent solution, dispersing the core in a silver ion solution, and sonicating to ensure uniform dispersion; Slowly adding a reducing agent solution while stirring to reduce the silver ions to nanosilver particles on the surface of the core; After the reaction is completed, the modified core is collected by centrifugation, and repeatedly washed with deionized water to remove unreacted silver salt and reducing agent; finally, the core is dried in a vacuum drying oven for later use; The core is surface grafted: Dissolving an appropriate amount of γ-aminopropyltriethoxysilane in anhydrous ethanol to form a modified solution; Dispersing the modified core in the modification solution and ultrasonically treating to ensure uniform dispersion; Allow to stand at room temperature to allow the silane coupling agent to undergo a chemical grafting reaction with the core surface; After the reaction, the functionalized microsphere cores were collected by centrifugation and repeatedly washed with anhydrous ethanol to remove the unreacted silane coupling agent; Finally, the microsphere core is dried in a vacuum drying oven for later use to obtain the modified core; Core coating: dissolving a polyurethane prepolymer or a polyacrylate prepolymer in tetrahydrofuran to form a prepolymer solution; Add an appropriate amount of cross-linking agent as needed to promote the subsequent cross-linking reaction; Dispersing the functionalized core in the prepolymer solution and sonicating to ensure uniform dispersion; Allowing the prepolymer to stand at room temperature to undergo a cross-linking reaction on the surface of the core to form a polymer shell layer; After the reaction is completed, the coated conductive polymer microspheres are collected by centrifugation and repeatedly washed with tetrahydrofuran to remove unreacted prepolymer and crosslinking agent; The conductive polymer microspheres are obtained by drying.

Citation Information

Patent Citations

  • Piezoelectric conductive epoxy resin composite damping material and preparation method thereof

    CN101392090A

  • High dielectric constant polypropylene composite and preparation method thereof

    CN108059767A

  • Graphene-containing self-repairing epoxy silver colloid

    CN108276929A

  • Low-temperature sintering conductive adhesive based on hybrid filler modification and preparation method thereof

    CN114907805A

  • Light high-strength electromagnetic shielding composite material based on conductive hollow microspheres as well as preparation method and application of light high-strength electromagnetic shielding composite material

    CN115340748A

Cited By

  • Preparation method of nano-copper-based conductive composite material

    CN121641592A

  • Preparation method of nano-copper-based conductive composite material

    CN121641592B